Enhancing Students’ Emotional Well-Being through a Peer Counseling Bootcamp - Jamain, Ririanti Rachmayanie; Zahidah, Asih Nor; Syammari, Shoofii; Hikmah, Nurul; Adawiyah, Rabiatul (Universitas Lambung Mangkurat, 2026)
SMP Negeri 24 Banjarmasin is situated in an area along the riverbank where incidents of bullying are still present. Students who experience bullying often struggle with low emotional well-being and require social support from their peers. The Mandatory Lecturer Service Program aimed to provide a bootcamp for OSIS members, enabling them to offer peer counseling and enhance emotional well-being in the school environment. The method of the Mandatory Lecturer Service Program was Participatory Action Research (PAR). A peer counseling bootcamp to enhance emotional well-being was held on September 3, 2025, at SMP Negeri 24 Banjarmasin. Ten OSIS members participated in this bootcamp. After participating in the bootcamp, students experienced an average increase in their emotional well-being of 7.42%. Additionally, the satisfaction evaluation of the bootcamp revealed an average score of 94%, indicating that the peer counseling bootcamp was beneficial for students in improving their emotional well-being and preventing bullying.